2016 6th IEEE International Conference on Biomedical Robotics and Biomechatronics (BioRob) 2016
DOI: 10.1109/biorob.2016.7523807
|View full text |Cite
|
Sign up to set email alerts
|

Gaze-based teleprosthetic enables intuitive continuous control of complex robot arm use: Writing & drawing

Abstract: Abstract-Eye tracking is a powerful mean for assistive technologies for people with movement disorders, paralysis and amputees. We present a highly intuitive eye tracking-controlled robot arm operating in 3-dimensional space based on the user's gaze target point that enables tele-writing and drawing. The usability and intuitive usage was assessed by a "tele"writing experiment with 8 subjects that learned to operate the system within minutes of first time use. These subjects were naive to the system and the tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Consequently we propose [3] how tracking the gaze position in 3D using our custom developed binocular 3D eye trackers (GT3D), provides a considerably richer signal directly relevant for robotic, exoskeleton and prosthetic control, overcoming the limitations of conventional BMI systems. We have since shown that such eye tracking can be used for precise robotic end-point control and manipulation in small 3D volumes [11] and for near instant ability to perform teleoperation tasks as painting in an oil brush technique [12], or navigate a wheelchair without requiring to interact with a user interface [13]. Here we demonstrate a novel technique for 3D calibration that enables us to quickly and accurately calibrate a UR-10 robotic arm in 3D space.…”
Section: Introductionmentioning
confidence: 92%
“…Consequently we propose [3] how tracking the gaze position in 3D using our custom developed binocular 3D eye trackers (GT3D), provides a considerably richer signal directly relevant for robotic, exoskeleton and prosthetic control, overcoming the limitations of conventional BMI systems. We have since shown that such eye tracking can be used for precise robotic end-point control and manipulation in small 3D volumes [11] and for near instant ability to perform teleoperation tasks as painting in an oil brush technique [12], or navigate a wheelchair without requiring to interact with a user interface [13]. Here we demonstrate a novel technique for 3D calibration that enables us to quickly and accurately calibrate a UR-10 robotic arm in 3D space.…”
Section: Introductionmentioning
confidence: 92%
“…In addition to head control methods discussed here, several alternate control interfaces to manual joysticks have been developed for individuals with severe movement impairments. These include sip-and-puff systems, voice control [24], gaze control [25] and tongue control [26]. These interfaces typically involve some tradeoff between (i) the number of control dimensions (e.g., a device that only allows control of 1 or 2 dimensions would require frequent 'switching' to control a high DOF robotic arm), (ii) the type of control (e.g., discrete controls are possible using voice commands but are less intuitive and precise relative to continuous control like a joystick), and (iii) the 'invasiveness' of the device both in terms of its physical attributes (e.g., whether it is easily wearable, wireless etc.)…”
Section: Plos Onementioning
confidence: 99%
“…Haddadin and Croft, 2016;Maurtua et al, 2016;Shafti et al, 2019a), or equipping them with additional arms to perform several tasks concurrently (e.g. Dziemian et al, 2016;Parietti and Asada, 2016). The latter fits within a particular area of human augmentation robotics which is referred to as supernumerary robotics.…”
Section: Introductionmentioning
confidence: 99%